Modified Carbon Nanotube Paste Electrode for Voltammetric Determination of Carbidopa, Folic Acid, and Tryptophan - Sakineh Esfandiari Baghbamidi; Hadi Beitollahi; Hassan Karimi-Maleh; Somayeh Soltani-Nejad; Vahhab Soltani-Nejad; Sara Roodsaz (Journal of Analytical Methods in Chemistry)
A simple and convenient method is described for voltammetric determination of carbidopa (CD), based on its electrochemical oxidation at a modified multiwall carbon nanotube paste electrode. Under optimized conditions, the proposed method exhibited acceptable analytical performances in terms of linearity (over the concentration range from 0.1 to 700.0 μM), detection limit (65.0 nM), and reproducibility (RSD=2.5%) for a solution containing CD. Also, square wave voltammetry (SWV) was used for simultaneous determination of CD, folic acid (FA), and tryptophan (TRP) at the modified electrode. To further validate its possible application, the method was used for the quantification of CD, FA, and TRP in urine samples.